Intercellular communication between extracellular vesicles from conditioned macrophages and breast cancer cells drives endocrine therapy resistance - María C. Rodriguez-Baili; Miguel Palma-Cobo; César G. Prucca; María Yáñez-Mó; German A. Gil (Frontiers in Cell and Developmental Biology)
IntroductionBreast cancer is a leading cause of cancer-related mortality among women, with nearly 70% of cases being estrogen receptor-positive (ER+). While endocrine therapies, such as tamoxifen, have significantly improved patient outcomes, resistance—whether intrinsic or acquired—remains a major clinical challenge that limits treatment efficacy. Emerging evidence suggests that endocrine resistance is often driven by the presence and expansion of cancer stem cells (CSCs), which contribute to recurrence, metastasis, and therapeutic failure. The tumor microenvironment (TME), including immune cells like macrophages, soluble factors, and extracellular vesicles (EVs), plays a crucial role in promoting tumor progression and therapy resistance. EVs are small lipid bilayer-bound particles that facilitate intercellular communication by transferring bioactive cargo capable of reprogramming recipient cells.MethodsTo investigate the role of macrophage-derived EVs in endocrine resistance, we isolated EVs from TNF-α-conditioned macrophages (TNF EVs) and treated MCF-7 ER+ breast cancer cells with these vesicles. We assessed changes in proliferation, migration, epithelial-mesenchymal transition (EMT), CSC-like properties, and tamoxifen resistance. Additionally, we evaluated whether tumor-derived EVs modulate macrophage polarization by analyzing the expression of PD-1 and other immunomodulatory markers.ResultsTNF EV-treated MCF-7 cells showed significantly increased proliferation, enhanced migratory behavior, and morphological changes associated with EMT. Importantly, treated cells developed a stem-like phenotype, characterized by a larger CD44High/CD24Low subpopulation and improved spheroid-forming ability. These features correlated with sustained proliferation even in the presence of tamoxifen, supporting the development of endocrine resistance. Furthermore, EVs derived from tumor cells triggered macrophage polarization toward a tumor-associated macrophage (TAM) profile, with increased PD-1 expression, indicating a role in immune suppression and tumor immune evasion.DiscussionThese findings emphasize the dual role of TNF-α-conditioned macrophage-derived EVs in driving both endocrine resistance and immune modulation in ER+ breast cancer. By promoting stemness, EMT, and tamoxifen resistance, as well as inducing immunosuppressive macrophage polarization, these EVs emerge as key contributors to tumor progression. Our study highlights the therapeutic potential of targeting EV-mediated communication to overcome endocrine resistance and enhance clinical outcomes for ER+ breast cancer patients. This work establishes a critical framework for future studies aimed at harnessing EVs as therapeutic targets or biomarkers in breast cancer management.